STRATEGI PROMOSI PAKET WISATA MANCANEGARA BIRO PERJALANAN WISATA FUN HOLIDAY DALAM MENARIK MINAT KONSUMEN - , FAARAH KAMELIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the travel agent that growth was Fun Holiday, that established since early 2012. But then, what becomes the problem is the package tours abroad, for the consumer is more interesting than domestic package tours in Fun Holiday. For that the writer wants to know what kind of promotion strategy did by Fun Holiday that offered towards package tours abroad. The reaserch method were by interview, by coming directly to the object, and then did some interview with marketing staff to get the complete data information. Literature study, by collecting data and information from the books that related to this reaserch. Documentation, reasercher gains document information such as image, photo, and attachment. From the reaserch, writer have some conclusion that consumer interested towards package tours abroad was quite high because Fun Holiday offered cheap price for package tours abroad. Thats why package tours abroad more desirable to consumer in Fun Holiday.